Experimental and numerical investigation of the primary breakup of an airblasted liquid sheet. (May 2017) - Warncke, K.; Gepperth, S.; Sauer, B.; Sadiki, A.; Janicka, J.; Koch, R.; Bauer, H.-J.
Highlights: Identical breakup phenomena are observed in experiment and simulation. Ligament and bag formation in the vicinity of the atomizing edge. Efficient characterization of the liquid sheet by tracking the phase interface. 3D-DNS data is analyzed as seen from the top corresponding to shadow images. Droplet size distributions provided by eDNS are in good agreement with the experiment. Abstract: The primary breakup of airblast atomization is governed by complex mechanisms and is still not well understood. In recent years high speed shadowgraphy experiments and Direct Numerical Simulations of prefilming airblast atomization have been performed independently. In this paper detailed results of a combined experimental and numerical study are presented. A single operating point of a planar prefilming airblast atomizer is investigated, based on a spatial resolution of 10 µm and a consistent analysis of the liquid film in both the experimental and the numerical studies. For the analysis the three-dimensional DNS data is projected on a plane, corresponding to the data obtained by shadowgraphy. The experiment is characterized by back light illumination in conjunction with particle and ligament tracking velocimetry. A Depth of Field correction is applied to further improve the measurement accuracy. For the numerical investigation the embedded DNS approach is utilized: The primary breakup region is simulated with a highly resolved DNS, embedded in a coarser Large Eddy Simulation. The comparison comprises a phenomenological discussion of the disintegration process and quantitative results. Distributions for the breakup length, the liquid film deformation velocity, the droplet sizes and velocities are presented. The results are in good agreement and confirm the applicability of the embedded DNS and the particle and ligament tracking velocimetry for the analysis of the primary breakup of airblast atomization. This work also shows the intrinsic limitation of a diffusive interface technique as the results depend on the filtering parameter of the diffuse interface.